Harga Transfer dan Kesulitan Keuangan sebagai Determinan dalam Praktik Penghindaran Pajak - Natasya Arifa Salsabila; Nera Marinda Machdar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Taxes play an important role in the economy as a source of state revenue that is used to fund various development programs. However, the practice of tax avoidance is often a challenge that is detrimental to the potential of state revenue and is the main issue in tax management. Researchers compiled this scientific article with the aim of exploring the link between transfer pricing and financial difficulties in influencing tax avoidance practices. The method used is literature study by analyzing various journals, books and relevant research reports through online platforms such as Google Scholar and Publish or Perish. The data was analyzed using a qualitative descriptive approach to identify patterns and understand the implications of the relationship between the variables studied. The results of the research findings suggest that the relationship between transfer prices and financial hardship to tax avoidance is inconsistent with mixed results. Some analyses showed a significant association, while others found no strong association. These findings indicate that the influence is situational and dependent on the characteristics of the company, thus expanding the understanding of the factors that affect tax avoidance and serving as a basis for further research.